Comparison of exergaming and vestibular training on gaze stability, balance, and gait performance of older adults: a single blind randomized control trail - Bukhari, Syeda Amna; Misbah Ghous; Butt, Poshmal; Khawar Kiyani, Sania; Tariq, Aroosa (Journal of the Pakistan Medical Association, 2022)
Objective: To compare the effects of exergaming and vestibular training on gaze stability, balance and gait performance of older adults. Method: The single-blind randomised controlled trial was conducted from August to October 2020 at the Doctor Raza Clinic, Swabi, Pakistan, and comprised individuals of both genders aged 60-75 years. The subjects were randomised into two groups using the sealed envelope method. Group 1 received exergaming, while group 2 received vestibular training 3 days a week for 6 weeks. The outcomes measures were dynamic gait index, time up and go test and non-instrumented dynamic visual acuity test. Data was analysed using SPSS 21. Results: Of the 24 subjects, 12(50%) were in each of the two groups. Overall, there were 16(66%) males and 8(33%) females with a mean age of 66.3±4.36 years. Intra-group improvement was significant compared to the baseline (p<0.05) in both the differences, but inter-group differences across all parameters were non-significant (p>0.05). Conclusion: Both exergaming and vestibular training has similar effects on gaze stability, balance, and gait performance among the older adults. Clinical Trials.gov Identifier: NCT04414462 Key Words: Exergaming, Vestibular training, Gaze stability, Older adults.